WASAR imaging with backprojection based group complex approximate message passing - Wei, Zhonghao; Jiang, Chenglong; Zhang, Bingchen; Bi, Hui; Hong, Wen; Wu, Yirong (Electronics letters, 2016)
Group sparsity based wide angle synthetic aperture radar imaging model is developed and propose a novel algorithm called backprojection based group complex approximate message passing to recover the anisotropic scene. Compared with conventional backprojection based complex approximate message passing algorithm for the recovery of isotropic scene, the proposed method accommodates aspect dependent scattering behaviour better and can produce better imagery. Simulated and experimental results are presented to demonstrate the validity of the proposed algorithm.